2009
DOI: 10.3402/jom.v1i0.1979
|View full text |Cite
|
Sign up to set email alerts
|

Tracking of plasma antibodies againstAggregatibacter actinomycetemcomitansandPorphyromonas gingivalisduring 15 years

Abstract: Background Plasma antibody measurements of antibody levels to periodontal pathogens may be used to support diagnosis, disease activity, classification, and prognosis of periodontitis.Objective The aim of this study was to investigate the long-term stability of plasma antibody levels against Aggregatibacter actinomycetemcomitans and Porphyromonas gingivalis.Design Plasma immunoglobulin G (IgG) antibody levels against the pathogens were analyzed annually during 15 years from 21 voluntary subjects, whose periodon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 30 publications
4
33
1
Order By: Relevance
“…Blood levels of antibodies to periodontal bacteria associated with periodontitis are stable over time [24,25], and do not change significantly following treatment [26]. However, the composition of periodontal biofilm may display variations according to the state of the disease [2426].…”
Section: Introductionmentioning
confidence: 99%
“…Blood levels of antibodies to periodontal bacteria associated with periodontitis are stable over time [24,25], and do not change significantly following treatment [26]. However, the composition of periodontal biofilm may display variations according to the state of the disease [2426].…”
Section: Introductionmentioning
confidence: 99%
“…Anti- Aa antibodies in patients with periodontitis show only minimal variation in titer over 15 years of follow up (19). Even with periodontal treatment, antibodies against Aa were shown to remain elevated over the duration of a 30-month period (20).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, no difference was found between groups for IgA class antibody levels. It has been shown that serum levels of IgG are not associated with periodontal disease activity, and IgG titres to periodontal bacteria remain elevated and stable over time,31 32 whereas serum levels of IgA seem to be linked to periodontal disease destruction and have a short life. The present study indicates original CV events are associated with a high exposure to periodontal bacteria and a strong humoral response, contrary to following events which seem to be characterised by a weak antibody response 33.…”
Section: Discussionmentioning
confidence: 99%